Toraja’s Carving Symbols and the Theological Meaning (Jurnal Keguruan dan Ilmu Pendidikan, 2018)
In the sense that God's salvation, we still have experienced in a sign or symbol that is the mystery of redemption that we experienced in the form of symbols.Thus the presence of Jesus Christ and His saving work in carving Toraja culture is presence in the form of signs or symbols. From the structure, symbols never appear for itself, but for which is symbolized. But what symbolized it can only be experienced and understood through the symbols. Therefore; culture is God’s manner to declared intention of His will and power to be able to dive in, to be understood and enjoyed by human beings, especially for the people of Toraja. Toraja society is a community that is rich with symbols narrated through engraving seen in traditional houses, fabrics and so on. The material presented in this section by the authors, only a fraction of the symbol in the Torajan’s people, who need to be revealed and given meaning in both the traditional order and culture, and in order of religiousness.